Selective Recovery of Molybdenum over Rhenium from Molybdenite Flue Dust Leaching Solution Using PC88A Extractant - Ali Entezari-Zarandi; Dariush Azizi; Pavel Anatolyevich Nikolaychuk; Faïçal Larachi; Louis-César Pasquier (Metals, 2020)
Selective solvent extraction of molybdenum over rhenium from molybdenite (MoS2) flue dust leaching solution was studied. In the present work, thermodynamic calculations of the chemical equilibria in aqueous solution were first performed, and the potential–pH diagram for the Mo–Re–<semantics><msubsup>SO42−</msubsup></semantics>–H2O system was constructed. With the gained insight on the system, 2-ethylhexyl phosphonic acid mono-(2-ethylhexyl)-ester (PC88A) diluted in kerosene was used as the extractant agent. Keeping constant the reaction temperature and aqueous-to-organic phase ratio (1:1), organic phase concentration and pH were the studied experimental variables. It was observed that by increasing the acidity of the solution and extractant concentration, selectivity towards Mo extraction increased, while the opposite was true for Re extraction. Selective Mo removal (+95%) from leach solution containing ca. 9 g/L Mo and 0.5 g/L Re was achieved when using an organic phase of 5% PC88A at pH = 0. No rhenium was coextracted during 10 min of extraction time at room temperature. Density functional theory (DFT) calculations were performed in order to study the interactions of organic extractants with Mo and Re ions, permitting a direct comparison of calculation results with the experimental data to estimate selectivity factors in Mo–Re separation. For this aim, PC88A and D2EHPA (di-(2-ethylhexyl) phosphoric acid) were simulated. The interaction energies of D2EHPA were shown to be higher than those of PC88A, which could be due to its stronger capability for complex formation. Besides, it was found that the interaction energies of both extractants follow this trend considering Mo species: <semantics><msubsup>MoO22+</msubsup></semantics> > <semantics><msubsup>MoO42−</msubsup></semantics>. It was also demonstrated through DFT calculations that the interaction energies of D2EHPA and PC88A with species are based on these trends, respectively: <semantics><msubsup>MoO22+</msubsup></semantics> > <semantics><msubsup>MoO42−</msubsup></semantics> > <semantics><msubsup>ReO4−</msubsup></semantics> and <semantics><msubsup>MoO22+</msubsup></semantics> > <semantics><msubsup>ReO4−</msubsup></semantics> > <semantics><msubsup>MoO42−</msubsup></semantics>, in qualitative agreement with the experimental findings.